SAT0379 Effects of Abatacept on Synovitis as Assessed by Magnetic Resonance Imaging (MRI) in Psoriatic Arthritis - Preliminary Analysis from A Single Centre, Placebo-Controlled, Crossover Study. (10th June 2014) - Szentpetery, A.; Heffernan, E.; Haroon, M.; Gallagher, P.; Baker, A.-M.; Cooney, M.; FitzGerald, O.
Abstract : Background: Abatacept, a soluble, fully human fusion protein which selectively inhibits T-cell activation via competitive binding to CD80/CD86, decreases serum levels of cytokines and inflammatory proteins implicated in the pathogenesis of psoriatic arthritis (PsA). It has been proposed that 10 mg/kg of abatacept, the approved dose for rheumatoid arthritis may be an effective treatment choice for PsA. [1] Objectives: (1) To study both skin and joint-related clinical outcomes prior to and 6 months after introducing abatacept treatment in PsA; (2) To investigate MRI changes of an inflamed knee joint over time in PsA patients on abatacept. Methods: 15 biological treatment-naïve PsA patients fulfilling the CASPAR criteria with active disease for ≥3 months (≥3 swollen and ≥3 tender joints) with clinical synovitis of a knee and the presence of a psoriatic skin lesion were enrolled in the study. Patients were randomised to receive abatacept 3mg/kg or placebo infusion on day 1, 15 and 29; thereafter abatacept 10mg/kg was administered to all patients every 28 days for 5 months. A stable dose of methotrexate (7.5-25 mgs/week) for >3 months prior to randomization was the only concomitant DMARD permitted. Gad-enhanced MRI of the same involved knee was performed at baseline, 2 and 6 months and scored using the PsAMRIS method by one consultant radiologist. For the semi-quantitative method each knee was divided into 4 anatomical regions; medial (MED) and lateral (LAT) parapateller recesses, intercondylar notch (ICN) and suprapatellar pouch (SPP). A synovitis score ranging from 0 to 3 was assigned to each region and then added to give a total MR synovitis score (MRS) ranging from 0 to 12. Results: At the time of the analysis, the study is still blinded and so the results discussed are the overall results from 14 of the 15 patients. Patients (8 female/6 male) mean age was 44.6 (±15.2) years. Four patients were on methotrexate with the remainder not receiving any DMARDs during the study. At baseline patients' mean DAS28-ESR was 4.9 (±1) and DAS28-CRP 4.8 (±0.8). Median PASI, HAQ, PsAQol and DLQI were 3.6 (0-9.6), 1 (0-2.125), 10.5 (1-17) and 2.5 (0-27) respectively. Mean synovitis scores at MED, LAT, ICN and SPP regions were 2.07 (±0.9), 2.21 (±0.9), 1.4 (±0.8) and 1.85 (±1) respectively at baseline; mean MRS was 7.6 (±3.4). As per EULAR criteria 87.5% of the patients responded to the treatment at 6 months; 75% judged a good responder. 68 tender and 66 swollen joint counts, duration of morning stiffness, global health score, DAS28-ESR, DAS28-CRP, HAQ and PsAQol reduced significantly at 6 months compared to baseline. While there was no significant difference compared to baseline in the 4 anatomical region scores, the median MRS decreased over the study period and was significantly lower at 6 months compared to baseline (p=0.016). Conclusions: These interim results show that 6 months of abatacept treatment reduced synovitis scores as assessed by MRI. Our results mirror the clinical improvements observed and support published data suggesting that 10 mg/kg of abatacept is a potent treatment option in PsA. References: Mease P et. al. Abatacept in the Treatment of Patients With Psoriatic Arthritis. Arthritis Rheum. 2011 Apr;63(4):939-48. Acknowledgements: This study received drug and financial support from Bristol Myers Squibb. Disclosure of Interest: A. Szentpetery: None declared, E. Heffernan: None declared, M. Haroon: None declared, P. Gallagher: None declared, A.-M. Baker: None declared, M. Cooney: None declared, O. FitzGerald Grant/research support: Pfizer, Abbott, BMS, MSD, Roche, UCB, Consultant for: Pfizer, Abbott, BMS, MSD, Janssen, Roche, Speakers bureau: Pfizer, Abbott, Janssen, Roche, UCB DOI: 10.1136/annrheumdis-2014-eular.5531